Penerapan Sapta Pesona Di Kelurahan Ledok, Kecamatan Argomulyo Kota Salatiga - Trenggono Trenggono; Aurillia Triani Aryaningtyas (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Sapta Pesona is a framework that promotes the attractiveness of Indonesian tourism through seven aspects, namely nature, attractions, accessibility, amenities, activities, security and cleanliness. This project involves collaboration with local communities, local government, and various stakeholders to achieve the following objectives: Increase community understanding of the Sapta Pesona concept and the importance of sustainable tourism practices. Empowering local communities in managing successful tourism businesses, such as homestays and traditional food stalls. Development of tourism infrastructure, including the construction of tourist facilities and adequate transportation routes. Implementation of a tourism promotion campaign to increase the visibility of Ledok Village as an attractive tourism destination. Through various training, education and promotional activities, the project aims to create a positive impact on the local economy, empower communities and promote responsible and sustainable tourism. The conclusion of this project reflects the results that have been achieved and recommendations for next steps in developing tourism in Ledok Village.